The Edinburgh companion to D.H. Lawrence and the arts - Brown, Catherine (Lecturer); Reid, Susan, 1965- (Edinburgh companions to literature and the humanities., 2020)
This book includes twenty-eight innovative chapters by specialists from across the arts, reassessing Lawrence's relationship to aesthetic categories and specific art forms in their historical and critical contexts.